AN ANALYSIS OF HIGHER ORDER THINKING SKILL IMPLEMENTATION IN ENGLISH READING TEXTBOOK FOR THE FIFTH GRADERS OF MALAYSIAN PRIMARY SCHOOL - Ahmad Ruhin Hidayat (Faculty of Education and Teachers Training, 2019)
Higher order thinking skill has become an interesting issue in educational terms including in Malaysia. Currently, teaching English in Malaysia is using a textbook as the main source. Reading is one of the skills which is known as a complex skill because it is well related to higher order thinking. The three higher levels of the cognitive domain in Bloom’s revised taxonomy are analysis (C4), evaluation (C5), and creation (C6). The objectives of the research are to know the types and the most frequent use of higher order thinking skill found in reading essay exercises of English textbook for the fifth graders of Malaysian Primary school. The study focuses on the cognitive process of the cognitive domain in Bloom’s revised taxonomy. The type of research is descriptive qualitative research. The technique of collecting data in this research is documentation technique. The writer finds that the distribution of higher order thinking skill is higher than the lower order thinking skill but it is still unequal between one domain to other domains. It needs improvement to make the distributions of the cognitive domain more balance.